Prostatic Leiomyoma: A Case Report. (11th November 2012) - Mellas, Soufiane; Bouchikhi, Ahmed Amine; Tazi, Mohammed-Fadl; Khallouk, Abdelhak; Elammari, Jalal-Eddin; El Fassi, Mohammed-Jamal; Farih, Moulay Hassan
Abstract : Prostatic enlargement due to benign adenomatous hyperplasia is very common in elderly males. However, benign mesenchymal tumors especially true leiomyoma of the prostate are rare. We describe a 68-year-old male presenting a urinary obstruction lasting more than two years. The patient was referred for an acute urinary retention. The clinical examination was normal. The perrectal examination revealed an enlarged prostate without abnormalities. An endoscopic resection was performed. The histopathological examination revealed a benign smooth muscle tumor with absence of glandular hyperplasia; the result was confirmed by immunohistochemistry. Accordingly, the diagnosis of true leiomyoma of the prostate was made.